Indicators that determine the physical readiness of young judokas aged 13-14 years for fights - Rakhlin M.A. ,; Bolotin A.E. ,; Vasiliev I. M. ,; Martynov D.I. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify indicators of physical readiness that influence the effectiveness of technical actions and attacking combinations of young judokas aged 13-14 years. Methods and structure of the study. The experiment was carried out in 2023 on the basis of a sports school, in which young judokas from the training group took part. The intensification of training tasks in the process of special motor training made it possible during the formative experiment to identify significant indicators of the development of speed, speed-strength, coordination abilities and speed endurance. Results and conclusions. To perform a series of throws with a two-handed grip, throws over the shoulder from a lapel grip and other complex technical combinations, agility, coordination of movements, speed and strength are required, since in a short period of time a judoka must assess the situation, instantly make the only correct decision and execute accurately technical action. Indicators of the degree of physical readiness of young judokas aged 13-14 years for competitive activities have been identified, contributing to the growth of technical and tactical skills.